2005
DOI: 10.1097/01.brs.0000195897.17277.67
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Charité Artificial Disc on the Implanted and Adjacent Spinal Segments Mechanics Using a Hybrid Testing Protocol

Abstract: The hybrid testing protocol is advocated because it better reproduces clinical observations in terms of motion following surgery, using pure moments. Using this approach, we found that the Charité artificial disc placement slightly increases motion at the implanted level, with a resultant increase in facet loading when compared to the adjacent segments, while the motions and loads decrease at the adjacent levels. However, in the load control mode that we believe is not that clinically relevant, there was a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
126
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(137 citation statements)
references
References 34 publications
11
126
0
Order By: Relevance
“…These results indicate that Dynesys can alleviate facet loading on the implanted level under extension, and they follow a similar trend to the results presented by Rohlmann [11]. Although FCF was noticeably increased at the adjacent levels, it remains much lower than the values of the fusion model (?169% under extension; ?28.9% under torsion) [20]. At present, several clinical reports have demonstrated that Dynesys implantation does not induce a problem in the adjacent facet joint [2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…These results indicate that Dynesys can alleviate facet loading on the implanted level under extension, and they follow a similar trend to the results presented by Rohlmann [11]. Although FCF was noticeably increased at the adjacent levels, it remains much lower than the values of the fusion model (?169% under extension; ?28.9% under torsion) [20]. At present, several clinical reports have demonstrated that Dynesys implantation does not induce a problem in the adjacent facet joint [2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 90%
“…For the convergence test, three mesh densities (coarse model: 4,750 elements/4,960 nodes; normal model: 27,244 elements/30,630 nodes; finest model: 112,174 elements/ 94,162 nodes) were selected to test the ROM changes in the INT model, and the finest mesh density was selected because the changes between the normal model and finest model were within 1.03% in flexion (\0.2°), 4.39% in extension (\0.5°), 0.01% in torsion (\0.2°), and 0.001% in lateral bending (\0.1°), respectively [20].…”
Section: Convergence Test and Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjacent level effects were analyzed using a modified hybrid flexibility-stiffness protocol [40] which is a modified form of the hybrid protocol promoted by Panjabi and colleagues [12,[26][27][28][29]. This analysis technique is graphically illustrated for the flexion-extension response of a typical specimen in Fig.…”
Section: Modified Hybrid Protocolmentioning
confidence: 99%
“…However, some of the studies that have been performed to study TDR's adjacent to fusions [10,25,34] did not apply hybrid testing methods [10,34], or applied bending using an offset shear force that resulted in combined bending and shear loading [25]. The kinematics of isolated or multiple total disc replacements and isolated fusions have also been studied in the past [5,12,26,27,40]. However, to the authors' knowledge, there are no biomechanical studies documenting the range of motion and quality of kinematics (i.e.…”
Section: Introductionmentioning
confidence: 99%